"A seiva de nossa terra": representações do sertão e do sertanejo a partir da trajetória política de José Bernardo de Medeiros, Rio Grande do Norte (1880-1988) - Freire, Dikson de Almeida (2022)
On this dissertation, we look into the political path of the sertanejo José Bernardo de Medeiros and how it was appropriated in order to create a representation, defining himself as a prominent figure in the political history of Rio Grande do Norte and also legitimizing the political groups that considered themselves heirs of his legacy. While he was alive, the political clashes by the end of the imperial period brought repercussion for José Bernardo at the pages of Rio Grande do Norte newspapers. After his passing, in 1907, comrades, relatives and memorialists took up writing about his political path and built a memoir about José Bernardo based on elements of the area where he was active (Sertões of Seridó) and personal characteristics (honesty, dedication, humbleness) that made him a role model, and example to be followed. To be able to understand the repercussion of these representations, we base ourselves the Cultural History tought by Roger Chartier, starting from the scheme of conceitual representation, appropriation and circulation, because it allows us to cast some reflexions as of how his political path was relevant. Concerning the memoir built by these representations, we take as reference the studies about the relationship between memory and history promoted by philosopher Paul Ricoeur and historians Enzo Traverso and Fernando Catroga. The sources used in our work were: Newspaper O Povo (1889-1892); the Instituto Historico e Geografico of Rio Grande do Norte magazine, IHGRN from 1907; the books: Caicó: Subsídios para a história completa do município, (Monteiro: 1945); Seridó (Medeiros: 1954); Caicó cem anos atrás (Medeiros Filho: 1988). At last, analyzing the main representations built around his political path, both before and after his passing, we are able to realize how the facts, events and status built José Bernardo a role as a guide of people from Seridó. A reference to be followed. Without lefting behind typical Sertão representations, quite offensive, associating him to geographical elements of the semi arid, like droughts, poverty, famine, hardship, Seridó countrymen are also seen as brave, fierce, honest, unsubmissive and resistant. José Bernardo, put as a leader of this people, also shared these same positive characteristics. He was the maximum exponent of that land, so he represented all these values.